Nigeria's 2015 general elections : continuity and change in electoral democracy - Hamalai, Ladi (Palgrave Macmillan, 2020)
Contents: 1. Introduction -- 2. Theoretical and Structural Issues in Nigerian Politics -- 3. Continuity and Change in Nigeria's Electoral Democracy -- 4. Party System and the Dominance of the People's Democratic Party, 1999-2015 -- 5. Trends in Voter Behaviour, 1999-2015 -- 6. Trends in Election Outcomes, 1999-2015 -- 7. Democratic Governance and Political Accountability, 1999-2014 -- 8. Electoral Reform and Electoral Administration, 1999-2015 -- 9. Party Politics in the 2015 Nigerian Elections -- 10. The 2015 Presidential Election -- 11. The 2015 National Assembly Election -- 12. The 2015 Gubernatorial Election -- 13. Conclusion: The 2015 Elections and the Future of Electoral Democracy.